Educación en tiempo de catástrofe: Estrategias de sanación a través del currículo intercultural chileno. - Soto, Valeska Díaz (European Review of Latin American & Caribbean Studies)
This paper examines the incorporation of ancestral Mapuche games into formal Chilean education as a pedagogical strategy for collective healing and social transformation. It argues that the inclusion of traditional games must move beyond isolated or symbolic initiatives toward a systematic implementation involving public policies, teacher education, and active collaboration with Indigenous communities. From an intercultural and decolonial perspective, the playing body is understood as a key mediator of the memory--identity--territory triad and as a living archive of historical experiences and knowledge. The study proposes that ancestral games function as a transformative healing process by challenging cultural hegemony and educational coloniality, activating community agency, and fostering cultural recognition as a basis for social justice. Although grounded in local contexts, these practices have multiscalar trans-formative potential, contributing to the reconfiguration of power relations and the development of critical intercultural education in contemporary Chile.